Ways of showing love in marriage- differences across family development stages - Mihić, Ivana (Array, 2012)
The underlying idea of the family development perspective is that family in whole undergoes continuous changes in number and structure of family roles as well as in quality of family relations as an expected result of developmental challenges. The aim of this research is to describe the changes in ways married couples express love in different stages of the family development. The total sample consisted of 456 married couples from Serbia, and 302 married couples from Croatia. In both samples the duration of marriage was from 1 month to 57 years. Around 20% of couples in both Serbia and Croatia have no children. The rest of the samples were, according to the age of the oldest child, divided into categories describing family development stages (families with young child, families with preschool age child, families with school age child, families with adolescent, launching children, families with adult child, families in later life-aging families). The Ways of Showing Love Scale (Huić, Kamenov & Jugović, 2010) measuring four expressive („communal orientation/sacrifice“ ; „emotional openness and support“ ; „physical affection“ ; „verbal affection/gifting“) and two instrumental factors („domestic instrumentality“ ; „public instrumentality“)was administered. The results indicate significant differences in overall ways of showing love in different family development stages in both Serbian and Croatian sample. Also, both men and women behave differently when expressing love in different stages of family development. This trend was observed in all measured expressive factors and public instrumentality, whereas domestic instrumentality tends to be more gender specific and stable across family development. In all stages of family development ways of showing love are significant correlates of marital satisfaction. However, significant differences have been observed in the ways that expressive and instrumental ways of showing love correlate to marital satisfaction in both Serbian and Croatian couples. Both developmental and cultural differences are discussed.